Analysis of risk factors for postoperative recurrence of stage I colorectal cancer: a retrospective analysis of a large population - Wang, Jiawei; Song, Zhangfa (Frontiers in Surgery, 2024)
Background Colorectal cancer (CRC) is the third most common cancer worldwide. Patients diagnosed with stage I CRC typically do not require postoperative adjuvant treatment. However, postoperative recurrence is present in at least 40% of patients with CRC and often occurs in those with stage I disease. This study aimed to elucidate the current status of recurrence and clinicopathological characteristics in patients with stage I CRC. Methods Data of indicated patients were obtained from 18 registries in Surveillance, Epidemiology, and End Results (SEER). The multivariable Fine–Gray regression model was used to identify the mortality risk of patients. Disparities in survival were analyzed using Kaplan–Meier curves. Logistic regression was employed to identify factors associated with recurrent risk overestimation. Results Our study indicated a recurrence rate of 15.04% (1,874/12,452) in stage I CRC cases. Notably, we identified race, age, T stage, and carcinoembryonic antigen (CEA) levels as independent risk factors for tumor recurrence, substantially impacting prognosis. Furthermore, gender, race (Black), age (>65 years), elevated CEA levels, and refusal or unknown status regarding radiotherapy significantly correlated with an adverse prognosis in patients with stage I CRC. Conclusions We identified certain key clinicopathological features of patients with stage I CRC and demonstrated the survival benefits of radiotherapy, offering a new perspective on stage I CRC follow-up and treatment recommendations.